Urologists' usage and perceptions of urological apps. (December 2014) - Dempster, Niall J; Risk, Rachel; Clark, Ross; Meddings, Robert N
We conducted a survey of urologists to document their patterns of app usage and perceptions of app quality, and to assess their interest in future app usage. The survey was sent to all urologists on the mailing list of the British Association of Urological Surgeons (BAUS) (n = 1613). A total of 115 responses were received (a response rate of 7%). Most respondents (89%) owned mobile devices capable of downloading apps. Most respondents (79%) used apps and about half (49%) used urological apps; the latter accessed a mean of 2.4 urological apps per month. Significantly more younger (defined as <45 years old) than older urologists used urological apps ( P < 0.001). Respondents' perception of the overall quality of apps produced for both urologists and patients was relatively low. The respondents' interest in future app usage was strong. There was greatest interest in apps such as logbooks or revalidation ones (87%), reference apps (86%) and ones which aided decision-making (85%). There was considerable support for the implementation of measures to provide urological app quality assurance; most respondents believed app peer review (78%) and validation (78%) would be beneficial and 48% supported regulatory oversight. There appears to be a need for high quality urological apps and opportunities therefore exist for national urological associations and academic units to lead developments.